Design and simulation of a solar PV system for BRAC University - Eshita, Shaika Tamanna; Hossain, Alima; Raihan, Md. Ovik (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.